Factors Associated With Nocturia-Related Quality of Life in Men With Lower Urinary Tract Symptoms and Treated With Tamsulosin Oral Controlled Absorption System in a Non-Interventional Study - Michel, Martin C.; Schumacher, Helmut; Mehlburger, Ludwig; de la Rosette, Jean J.M.C.H. (Frontiers in Pharmacology, 2020)
Nocturia impairs quality of life (QoL). We have performed a non-interventional study in which men with lower urinary tract symptoms (LUTS) were treated for at least 3 months with tamsulosin oral controlled absorption system (0.4 mg q.d.). Other than observing efficacy and tolerability of this drug formulation, the study was designed to explore the relative roles of number of nocturia episodes and of non-urological causes of nocturia on nocturia-related QoL at baseline and treatment-associated changes thereof. The study enrolled 5775 men seeking treatment of their LUTS. Tamsulosin improved LUTS, e.g. International Prostate Symptom Score from 19.5 ± 5.9 to 10.1 ± 4.9 (means ± SD). This was associated by clinically meaningful improvements in the Nocturia QoL score (from 45 ± 19 to 73 ± 17 points) and other QoL scores. Number of nocturnal voids was the key driver of all QoL scores at baseline; change of number of nocturia episodes that of improvement of all QoL scores upon treatment. In contrast, non-urological causes of nocturia such as heart failure, diabetes, sleep apnea, fluid or alcohol intake or use of diuretics or hypnotics had only small if any effects on baseline QoL or treatment-associated improvements thereof. The observed effects of non-urological causes on QoL apparently were largely driven by their effect on number of nocturnal voids. These data further support the idea that improvement of nocturia may be an important treatment goal in male LUTS.